2018
DOI: 10.1140/epjc/s10052-018-5913-y
|View full text |Cite
|
Sign up to set email alerts
|

The $$f(R,T^\phi )$$ f ( R , T ϕ ) gravity models with conservation of energy–momentum tensor

Abstract: In this paper, we have derived a spatially flat homogeneous and isotropic cosmological model in f (R, T φ ) gravity with a scalar field. In addition to a minimally coupled scalar field with self interacting potential, we also have a contribution from the coupling of the geometry and the field. We have reconstructed a form of f (R, T φ ) by requiring the conservation of energy-momentum tensor of the scalar field. The behavior of the reconstructed f (R, T φ ) gravity is examined for a flat potential as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…In Ref. [90], two of the present authors studied such a case. For a complete discussion on this, we would like to refer to a recent study [91].…”
Section: The Model In F (R T) Gravitymentioning
confidence: 96%
See 1 more Smart Citation
“…In Ref. [90], two of the present authors studied such a case. For a complete discussion on this, we would like to refer to a recent study [91].…”
Section: The Model In F (R T) Gravitymentioning
confidence: 96%
“…It is well known that the conservation equation does not necessarily hold in f (R, T) gravity -see appendix A. Moreover, a scalar field with flat potential was studied earlier in the f (R, T) = R + 2 f (T) theory of gravity [90], looking for conditions for energy conservation. Surprisingly, it was found that the expression f (R, T) = R + 2 f (T) had the same form as before, viz., f (R, T) = R + 2λT.…”
Section: The Model In F (R T) Gravitymentioning
confidence: 99%
“…Eq. (66) shows that the motion is non-geodesic and the extra force F λ is perpendicular to the four-velocity u λ , i.e.…”
Section: Extra Forcementioning
confidence: 99%
“…For f (R, T φ ), see Ref. [66]. Here the authors constrained the field equations by a specific ansatz on the shape of starting function.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we will use the framework of f (R, T f ) gravity where T f stands for trace of energy momentum tensor of scalar field f. The authors in [4] have discussed the cosmic evolution in f (R, T f ) context. The authors in [5] investigated a flat homogeneous and isotropic cosmos in f (R, T f ) background. To reconstruct the models of f (R, T f ), they considered a massless scalar field with its corresponding potential.…”
Section: Introductionmentioning
confidence: 99%